2017
DOI: 10.1160/th16-10-0762
|View full text |Cite
|
Sign up to set email alerts
|

The fifth epidermal growth factor like region of thrombomodulin alleviates LPS-induced sepsis through interacting with GPR15

Abstract: Thrombomodulin (TM) exerts cytoprotection via the fifth region of epidermal growth factor (EGF)-like domain of TM (TME5) by interacting with G-protein coupled receptor 15 (GPR15) expressed on cell surface of vascular endothelial cells. TM is also implied to mediate anti-inflammatory functions by unknown mechanism. By applying a lipopolysaccharide (LPS)-induced murine sepsis model, we assessed the role of TME5 in septic inflammation and coagulation. We found that TME5 treatment protected mice in association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…GPR15 was also found to mediate homing of dendritic epidermal T-cells to skin in fetal mice, possibly contributing to the establishment of skin barrier function ( Lahl et al , 2014 ). In addition, a more recent study revealed an anti-inflammatory function of GPR15 in vascular endothelial cells ( Pan et al , 2017 ). Collectively these findings highlight GPR15 as a novel therapeutic target of immune disorders and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…GPR15 was also found to mediate homing of dendritic epidermal T-cells to skin in fetal mice, possibly contributing to the establishment of skin barrier function ( Lahl et al , 2014 ). In addition, a more recent study revealed an anti-inflammatory function of GPR15 in vascular endothelial cells ( Pan et al , 2017 ). Collectively these findings highlight GPR15 as a novel therapeutic target of immune disorders and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“… 37 Of note, the use of TME5 significantly alleviated graft- versus -host disease (GvHD) in a murine model. 37 TME5 also rescues mice from LPS-induced sepsis, 26 further confirming the anti-inflammatory function of TME5C.…”
Section: Discussionmentioning
confidence: 52%
“…Our previous study found that the cytoprotective effects of TM were preserved in TME5. 24 , 26 TME5 consists of three loops: A, B, and C ( Figure 1A ). The C-loop in the C-terminal subdomain is formed by a stretch of amino acids between the fifth and sixth cysteine residues, and its amino acid sequence is longer than those of the other two loops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR15 is also involved in the intestinal immune homeostasis in mice (but not humans) via its regulation of the local Treg cell compartment [65,66]. The two identified ligands, a thrombomodulin-derived protein fragment [67] and C10ORF99-encoded protein GPR15L [68], do not mediate 10 chemotaxis of GPR15 + cells, suggesting that a migration-unrelated mechanism underlies the GPR15 controlled processes in tissue immune homeostasis.…”
Section: Ccr6 -Ccr6 Is Broadly Expressed On Memory T Cells Includingmentioning
confidence: 99%